Randomised controlled trial of GP-led in-hospital management of homeless people ('Pathway'). - Hewett, N; Buchman, P; Musariri, J; Sargeant, C; Johnson, P; Abeysekera, K; Grant, L; Oliver, E; Eleftheriades, C; McCormick, B; Halligan, A; Marlin, N; et al. (Royal College of Physicians, 2016)
Homeless people have complex problems. GP enhanced care (Pathway) has shown benefits. We performed a randomised, -parallel arm trial at two large inner city hospitals. Inpatient homeless adults were randomly allocated to either standard care (all management by the hospital-based clinical team) or enhanced care with input from a homeless care team. The hospital data system provided healthcare usage information, and we used questionnaires to assess quality of life. 206 patients were allocated to enhanced care and 204 to usual care. Length of stay (up to 90 days after admission) did not differ between groups (standard care 14.0 days, enhanced care 13.3 days). Average reattendance at the emergency department within a year was 5.8 visits in the standard care group and 4.8 visits with enhanced care, but this decrease was not significant. -Quality of life scores after discharge (in 108 patients) improved with enhanced care (EQ-5D-5L score increased by 0.12 [95% CI 0.032 to 0.22] compared wtih 0.03 [-0.1 to 0.15; p=0.076] with standard care). The proportion of people sleeping on the streets after discharge was 14.6% in the standard care arm and 3.8% in the enhanced care arm (p=0.034). The quality-of-life cost per quality-adjusted life-year was £26,000. The Pathway approach doesn't alter length of stay but improves quality of life and reduces street -homelessness.